A STUDY ON CLOUD BASED BIO-SIGNALS MANAGEMENT FRAMEWORK - Panigrahi, Siddharth Arun; V, Umamaheswari (Asian Journal of Pharmaceutical and Clinical Research, 2017)
An analytical study of the complete framework for the management of biosignals is done. The framework provides for the acquisition, and storage of the biosignals, along with the associated metadata. It also provides solutions for validation, synchronization of acquired signals, thus allowing error-free signal inputs for further statistical analysis. The model comprises primarily of four layers, namely, acquisition, validation, post-processing and statistical analysis layers. Additionally, a presentation layer is also provided, wherein the appropriate end-user can use a suitable client or Web service to access the results of the statistical analysis. The raw data is deliberately spilt into two: Internal data (actual signal data) and External data (metadata) and they interact only when necessary (e.g. Identifying the biosignal's origin). Microservices are used to compartmentalize the functionalities required in the system. Additional solutions to problems plaguing the present models (like cloud-upload bottleneck) are also discussed. Â